(untitled) (Journal of the College of Basic Education, 2022)
The research aims to 1) Know the geographical concepts of children enrolled and not enrolled in kindergartenIn order to achieve the objectives of the research, the researcher developed hypotheses that are suitable for her research. The sample of the current research was limited to a sample of first-grade students enrolled and not enrolled in kindergarten. The sample was chosen by the researcher in a random manner, which amounted to (100) male and female students distributed among five primary schools for each school. 20 male and female students, 10 of whom had previously attended kindergarten and 10 had not previously attended. Kindergarten. In view of the absence of a local or Arab tool, or the presence of a foreign scale codified on the Iraqi environment to measure geographical concepts among kindergarten children, as far as the researcher knows, in order to identify geographical concepts among children.